Who provides follow-up care for patients with early breast cancer? - Worster, A. (College of Family Physicians of Canada, 1995)
OBJECTIVE: To assess how often family physicians are involved in posttreatment care of their stage I breast cancer patients and to identify factors associated with family physicians providing follow-up care. DESIGN: A retrospective cohort study with a 5-year follow up by chart review. PARTICIPANTS: All cases of breast cancer seen at the London Regional Cancer Centre between 1982 and 1987 were reviewed to identify 183 stage I cancer patients alive at 5 years. MAIN OUTCOME MEASURES: Whether a physician (other than an oncologist) was involved in the follow-up care of patients, and whether the physician was a family physician or a surgeon. RESULTS: Follow-up care during the 5-year postoperative period was provided in most cases by oncologists alone (66.7%); family physicians and surgeons were involved in 17.5% and 15.8% of cases, respectively. Surgeons became involved in follow-up care much earlier (12 months) than family physicians did (23 months) (P = 0.01) and were more likely to provide care for patients who received radiation treatment (P = 0.04) and for patients who lived in London (P = 0.004). Most malignant breast lesions (77.5%) were discovered by patients themselves (P = 0.0001). CONCLUSIONS: Currently, family physicians are infrequently involved in follow-up care of their patients with early breast cancer.